Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1016/0002-9343(91)90660-p
|View full text |Cite
|
Sign up to set email alerts
|

Preventability of emergent hospital readmission

Abstract: To determine whether emergent readmissions within 30 days of discharge are potentially preventable, we prospectively studied all readmissions to the medical service of a university teaching hospital during a 4-month period. The 327 readmissions, including 42 patients who were readmitted more than once during the study period, accounted for 12% of medical admissions. Nearly 75% of readmissions were due to previously diagnosed medical conditions; complications of drugs or therapeutic procedures caused 29%, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 14 publications
4
105
0
6
Order By: Relevance
“…However, in a rigorously designed randomized clinical trial, Naylor and associates (1999) found that within 24 weeks after discharge the readmission rate in the intervention group was lower than that in the control group (6.2% vs. 14.5%). In another article researchers reported the finding that only 8.8% of readmissions are preventable (Frankl, Breeling, & Goldman, 1991); in contrast, Graham and Some data were missing in these variables of family caregiver characteristics. Livesley (1983) stated that 47.7% of readmissions are preventable.…”
Section: Effectiveness Of Discharge Planning/dai Et Almentioning
confidence: 97%
“…However, in a rigorously designed randomized clinical trial, Naylor and associates (1999) found that within 24 weeks after discharge the readmission rate in the intervention group was lower than that in the control group (6.2% vs. 14.5%). In another article researchers reported the finding that only 8.8% of readmissions are preventable (Frankl, Breeling, & Goldman, 1991); in contrast, Graham and Some data were missing in these variables of family caregiver characteristics. Livesley (1983) stated that 47.7% of readmissions are preventable.…”
Section: Effectiveness Of Discharge Planning/dai Et Almentioning
confidence: 97%
“…Four studies did not specify the criteria used to classify readmissions, stating that reviewers judged which readmissions were avoidable. 12,17,25,26 Eleven studies described criteria that were subjective, citing few or no qualifiers or guides for reviewers. 6,13,14,16,21,22,24,31,35,37,38 Three studies used criteria that focused exclusively on adverse drug reactions.…”
Section: −38mentioning
confidence: 99%
“…No obstante, en parte relacionado con la diferente terminología empleada, también se ha dudado de su utilidad como índi-ce general (6,10), aunque en determinados procesos clínicos (p. ej., insuficiencia cardiaca, asma bronquial) la tasa de reingreso puede identificar problemas en la calidad asistencial (5,7,(11)(12)(13).…”
Section: Discussionunclassified